Familial Hypoparathyroidism with Pregnancy- Challenging Issue for Patient as well as for Physician (Faridpur Medical College Journal, 2011)
Familial hypoparathyroidism is a rare cause of hypoparathyroidism. It may be x-linked recessive, autosomal dominant or autosomal recessive. In autosomal dominant hypoparathyroidism there is activating mutation of the calcium sensing receptor leading to inhibition of Parathormone (PTH) secretion at inappropriately low serum ionized calcium level. The disease often manifests in the first decade but may appear later. Clinical signs primarily involving neuromuscular disturbances including generalized seizure. Management of pregnancy in hypoparathyroidism is challenging as both under treatment and over treatment is dangerous for fetus. Treatment of hypoparathyroidism in pregnancy includes combination of oral calcium supplementation with calcitriol with an aim to keep serum calcium within normal range. Here we discussed a case of 21 year pregnant lady with familial hypoparathyroidism with successful delivery of a healthy baby. Key words: Hypoparathyroidism; Hypocalcaemia; Hyperphosphataemia; Epilepsy. DOI: http://dx.doi.org/10.3329/fmcj.v6i2.9215 FMCJ 2011; 6(2): 113-115